A style discussion of Jeanne Zaidel-Rudolph’s Pendulum for Piano and Orchestra and a comprehensive catalogue of her orchestral, chamber and piano compositions - Johnson, Alexander F. (University of Pretoria, 2023)
Thesis (DMus (Musicology))--University of Pretoria, 2022.